BEKAS BENTENG-BENTENG BELANDA DI JAWA: PENGGUNAAN DAN "PENYALAHGUNAANNYA" - Novida Abbas (Berkala Arkeologi, 2002)
Archaeological remains in the form of a fort are one of the problems in cultural resource management. On the one hand, it appears that these fortresses need attention and need to be preserved, but on the other hand, various factors appear to be less supportive of the efforts towards preservation. It is hoped that with the growing interest in the preservation of various cultural heritages, the remains in the form of a fort can be "touched" by these efforts, before what is left is really only a fragment of the story.